Perovskite Crystallization: A‐Site Management for Highly Crystalline Perovskites (Adv. Mater. 4/2020). Issue 4 (27th January 2020) - Si, Haonan; Zhang, Zheng; Liao, Qingliang; Zhang, Guangjie; Ou, Yang; Zhang, Suicai; Wu, Hualin; Wu, Jing; Kang, Zhuo; Zhang, Yue
Abstract : In article number 1904702, Zhuo Kang, Yue Zhang, and co‐workers propose a concept of A‐site management by introducing an A‐site placeholder cation NH4 + during the perovskite crystallization process to balance the supersaturation discrepancy between AX and BX2 so as to improve its crystal quality without any residue. Such methodology successfully provides guidance for synthesis route design of highly crystalline perovskites.